REVOLUSI DESA BANYUWANGI DENGAN TEH CINDY; MENGOPTIMALKAN POTENSI LOKAL MELALUI PLATFORM DIGITAL - Rahmawati, Ima; Hasanah, Siti Lutfiatul; Maulana, Agung; Maulana, Muhammad Restu; Mulyati, Embun; Lestari, Hana (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
After conducting a survey, we found several obstacles in Banyuwangi Village, especially in the MSME sector which has difficulties related to marketing, access to information, and business legality. INAIS Sahid Bogor KKN students also identified a lack of coordination between the community and the village. Teh Cindi application is a digital solution to facilitate product marketing, provide the